You cannot assess until you measure it: using psoas index for measuring frailty - Kim, Ho Jin (Journal of Thoracic Disease; Vol 10, No 12 (December 30, 2018): Journal of Thoracic Disease, 2018)
Due to the increasing incidence of more complex heart diseases with the aging population, cardiac surgeons are having difficulties in determining who is most likely to benefit from a surgical intervention with a minimum risk of mortality and morbidity. In particular, the assessment of operative risk has become more critical in patients with severe aortic stenosis, owing to the successful employment of alternative transcatheter therapy. Several risk prediction models, such as the Society of Thoracic Surgeons (STS) Predicted Risk of Mortality and Morbidity and the European System for Cardiac Operative Risk Evaluation (euroSCORE) II, have been widely used to provide relevant information to cardiac surgeons for the assessment of the risk of cardiac surgery.